Saccadic eye movements as markers of schizophrenia spectrum: Exploration in at-risk mental states - Caldani, Simona; Bucci, Maria Pia; Lamy, Jean-Charles; Seassau, Magali; Bendjemaa, Narjes; Gadel, Rémi; Gaillard, Raphael; Krebs, Marie-Odile; Amado, Isabelle (Schizophrenia research, 2017)
Schizophrenia is a neurodevelopmental disease with cognitive and motor impairments. Motor dysfunctions, such as eye movements or Neurological Soft Signs (NSS), are proposed as endophenotypic markers. Antisaccade (AS) and memory-guided saccades (MGS), two markers of inhibitory control mechanism, are altered in both patients with schizophrenia and their relatives, although these tools may have different sensitivities. Recently, emphasis has been put on identifying markers predictive of psychosis transition in subjects with ultra-high-risk psychosis in order to develop targeted prevention. This study investigates AS and MGS in 46 patients with schizophrenia, 23 ultra-high-risk subjects, and 39 full siblings compared to 47 healthy volunteers. NSS were assessed as a marker of abnormal neurodevelopment. The results revealed more errors in MGS in patients, ultra-high-risk subjects and siblings, than in controls, and more specifically ultra-high-risk subjects with high NSS scores. By contrast, the error rate in AS was significantly higher only in patients with schizophrenia compared to controls. These findings suggest that MGS could be more accurate to detect deficient inhibitory processes as a marker of vulnerability before the onset of schizophrenia. The use of the different paradigms (AS, MGS) revealed distinct profiles depending on the stage of the disease, indicating that some alterations could be pure endophenotypic markers of vulnerability for schizophrenia, while others could be markers of the disease progression.